New service development strategy and process: considering concepts from financial sector in an analysis of the hospitality sector in Kenya - Oduori, Fredrick Nyongesa (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.